2006
DOI: 10.1373/clinchem.2005.060665
|View full text |Cite
|
Sign up to set email alerts
|

High Maternal Blood S100B Concentrations in Pregnancies Complicated by Intrauterine Growth Restriction and Intraventricular Hemorrhage

Abstract: Background: Intrauterine growth restriction (IUGR) is associated with perinatal mortality and with neurologic damage from intraventricular hemorrhage (IVH). We investigated whether S100B, a neural protein found in high concentrations after cell injury in the nervous system, is increased in serum of women whose pregnancies are complicated by IUGR and whose newborns develop IVH. We also explored the prognostic accuracy of maternal serum S100B for IVH in the newborn. Methods: We conducted a case-control study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 38 publications
3
24
0
1
Order By: Relevance
“…S100B was also higher in IUGR fetuses with redistribution of fetal-placental blood flow, the so called 'brain sparing effect', and correlated with the degree of fetal hemodynamic impairment, as indicated by an altered middle cerebral artery Doppler pattern, whereas IUGR fetuses without 'brain sparing effect' showed S100B concentrations similar to those of non-IUGR fetuses [31]. More recently, S100B was also measured in the blood of women whose pregnancies were complicated by IUGR and their newborns by IVH [32]. At times before clinical, laboratory, and ultrasound patterns can identify risk of IVH, maternal S100B was higher in IUGR pregnancies complicated by IVH than in those that were not and in unaffected pregnancies.…”
Section: Adrenomedullin Perinatal Asphyxia and Reperfusion Injurymentioning
confidence: 98%
See 1 more Smart Citation
“…S100B was also higher in IUGR fetuses with redistribution of fetal-placental blood flow, the so called 'brain sparing effect', and correlated with the degree of fetal hemodynamic impairment, as indicated by an altered middle cerebral artery Doppler pattern, whereas IUGR fetuses without 'brain sparing effect' showed S100B concentrations similar to those of non-IUGR fetuses [31]. More recently, S100B was also measured in the blood of women whose pregnancies were complicated by IUGR and their newborns by IVH [32]. At times before clinical, laboratory, and ultrasound patterns can identify risk of IVH, maternal S100B was higher in IUGR pregnancies complicated by IVH than in those that were not and in unaffected pregnancies.…”
Section: Adrenomedullin Perinatal Asphyxia and Reperfusion Injurymentioning
confidence: 98%
“…At times before clinical, laboratory, and ultrasound patterns can identify risk of IVH, maternal S100B was higher in IUGR pregnancies complicated by IVH than in those that were not and in unaffected pregnancies. At a cut-off of 0.72 mg/l, sensitivity was 100% and specificity was 99.3% for prediction of IVH [32]. S100B is also measurable in urine, and a normality reference curve, gestational age dependent, in urine of healthy preterm and term newborns has been performed [33].…”
Section: Adrenomedullin Perinatal Asphyxia and Reperfusion Injurymentioning
confidence: 99%
“…30 The low molecular weight of S100B would allow it to cross the placenta and reach the maternal circulation, as occurs also in intrauterine fetal growth restriction when brain damage occurs. 30 Finally, S100B protein has been shown, by immunohistochemistry, to be localized in villous and intermediate trophoblast cells of the normal human placenta at different trimesters of gestation, 15,31,32 although data in the sheep are lacking. Therefore, the hypothesis that part of S100B found in blood of preterm sheep might be from placental origin cannot be ruled out, although at present it can only be regarded as a speculation.…”
Section: Panel Bmentioning
confidence: 99%
“…Raised levels in neonatal, maternal and umbilical cord blood have been reported in FGR and neonatal cerebral hypoxia [24][25][26] . Moreover, S100β levels correlate with the severity of disease [27] , making it a useful tool in the evaluation of neurological disability of perinatal origin. Animal experimentation has shown that mild chronic hypoxia causes neurological dysfunction through an impaired development of neural processes and connections, while severe hypoxia causes direct damage to neuronal tissue and cell destruction [3] .…”
Section: Interpretation Of the Findings And Comparison With The Litermentioning
confidence: 99%